2016
DOI: 10.1038/nprot.2016.022
|View full text |Cite
|
Sign up to set email alerts
|

Interferometric scattering microscopy and its combination with single-molecule fluorescence imaging

Abstract: Interferometric scattering microscopy (iSCAT) is a light scattering-based imaging modality that offers a unique combination of imaging speed and precision for tracking nanoscopic labels and enables label-free optical sensing down to the single-molecule level. In contrast to fluorescence, iSCAT does not suffer from limitations associated with dye photochemistry and photophysics, or the requirement for fluorescent labeling. Here we present a protocol for constructing an iSCAT microscope from commercially availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
158
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(171 citation statements)
references
References 35 publications
0
158
0
Order By: Relevance
“…We used a custom-built iSCAT microscope2324 to follow the colloidal aggregate dynamics and perovskite crystal growth. The microscope set-up is as follows.…”
Section: Methodsmentioning
confidence: 99%
“…We used a custom-built iSCAT microscope2324 to follow the colloidal aggregate dynamics and perovskite crystal growth. The microscope set-up is as follows.…”
Section: Methodsmentioning
confidence: 99%
“…These features are time invariant, do not change with lateral sample displacements, and can therefore be removed. We call the process of isolating and subsequently removing these signatures “flat-fielding” (Arroyo, Cole, & Kukura, 2016). First, the sample is translated laterally while recording a stack of 100 images.…”
Section: Methods and Protocolsmentioning
confidence: 99%
“…3a) and iSCAT imaging of unlabeled microtubules revealed that EB3 decorated growing plus and minus ends of wt microtubules in the expected comet-like manner ( Fig. 2a-b, Supplementary Video 4) 12,13,16 . In clear contrast, EB3 decorated the entire lattice of GTPasedeficient E254A mutant microtubules ( Fig.…”
mentioning
confidence: 92%
“…3i). Quantitative analysis of the intensity profiles allows to extract the characteristic comet lengths and, knowing the measured growth speeds, also the lifetime of the EB3 binding sites 12,13,17,26 . This revealed a four-fold increase in the lifetime of the EB3 binding sites at the ends of E254D microtubules compared to wt microtubules (Fig 3i).…”
mentioning
confidence: 99%